Lumateperone tosylate, A Selective and Concurrent Modulator of Serotonin, Dopamine, and Glutamate, in the Treatment of Schizophrenia - Kunal Maini; Janice W. Hollier; Haley Gould; Victoria Bollich; John LaForge; Elyse M. Cornett; Amber N. Edinoff; Adam M. Kaye; Alan D. Kaye (Health Psychology Research)
# Purpose of Review